Information, deliberation, and decisional control preferences for participation in medical decision‐making and its influencing factors among Chinese cancer patients - Lin Xiao; Meifang Peng; Yawei Liu; Lili Zhang (Wiley, 2021)
Abstract Background Patient‐centred care should strive to respond to the individual patient's needs and preferences when possible. Yet, preferences of cancer patients for participation in different stages of the medical decision‐making process to increase matching of preferred and actual participation of the patients in decision‐making are not well known. Objective This study aimed to determine the level of information, deliberation and decisional control preferences in decision‐making practices among Chinese cancer patients and to explore their association with the sociodemographic and clinical variables of the patients. Methods A cross‐sectional study was conducted involving a convenience sample of 328 cancer patients from three public hospitals in Guangzhou, China. The Patient Expectation for Participation in Medical Decision‐making Scale (PEPMDS) was used to evaluate information, deliberation and decisional control preferences of the patients. Binary logistic regressions were conducted to determine the association between sociodemographic variables, clinical variables and preferences of the patients. Results Most patients reported a high preference for information (73.2%) and deliberation (73.8%), while a small number (37.2%) reported a high preference for decisional control. Younger patients and patients with higher levels of education were significantly more likely to have a high preference for information, deliberation and decisional control. Patients with low annual family incomes were significantly more likely to have a low preference for decisional control. Conclusion Preferences of patients for involvement in different stages of decision‐making practices could vary. The level of preferences appears to be related to the patient's age, education level, and financial status. Practice Implications Healthcare providers should tailor the participatory approaches of patients considering individual preferences for information, deliberation and decisional control during medical decision‐making. Patient Contribution Patients participated in the survey and filled in the questionnaires.